Predictors of Outcomes in the Treatment of Urge Urinary Incontinence in Women - Richter, Holly E. (2009)
INTRODUCTION AND HYPOTHESES: Women with urge predominant urinary incontinence (UUI) received active intervention (drug therapy alone or combined with behavioral therapy) for 10 weeks, then stopped all therapy and were followed for 6 more months. In this planned secondary analysis, we aimed to identify predictors of therapeutic success at 10 weeks (≥70% reduction in incontinence) and of ability to discontinue treatment and sustain improvements 6 months later. METHODS: Using data from 307 women, we performed logistic regression to identify predictors for outcomes described above. RESULTS: After controlling for group, only younger age was associated with short-term success (OR:0.8, 95% CI:0.66,0.96). At 6 months, controlling for group and short-term outcome, only greater anterior vaginal wall prolapse was associated with successful discontinuation (POP-Q point Aa; OR:1.33, 95% CI:1.03,1.7). CONCLUSION: These findings are not of sufficient strength to justify withholding conservative therapies, but might be used to promote realistic expectations when counseling patients.